Performance evaluation of water collection systems for a hybrid dephlegmator - Plessis, Jacques du; Reuter, Hanno C.R. (Applied thermal engineering, 2016)
•A water collection system is investigated to determine its collection effectiveness, drainage capability and pressure drop.•Modifications are made that increase the collection effectiveness from 92% to 100%.•Parametric CFD models are used to determine the loss coefficients for the trough and various basin systems designs.•Empirical relations are proposed using the parametric CFD models.•A comparison shows that the trough system generally has the lowest loss coefficient and pumping head requirements. Trough and basin water collection systems are used in wet-cooling towers and evaporative air-cooled heat exchangers to collect cooling or deluge water below the fill or heat exchanger bundle at the air inlet. Trough systems typically collect water in overlapping parallel troughs while allowing air to pass upwards between the troughs, whereas basin systems collect the water in a basin and the air enters laterally above the basin edge. The novel hybrid (dry/wet) dephlegmator (HDWD) requires a deluge water collection system supported high above the ground. A trough system is therefore considered the best option for this application. Apart from patents, limited information is found on the design and air-side loss coefficients of such systems and how they compare to equivalent basin systems. An existing trough collection system is therefore investigated experimentally to determine its collection effectiveness and drainage capability and to measure pressure drop characteristics. Modifications are made that increase the collection effectiveness from 92% to 100%. Parametric CFD models are developed and used to determine the loss coefficients for the trough and various basin system designs and empirical relations are proposed. A comparison shows that the trough system generally has the lowest loss coefficient and pumping head requirements.